On the heat waves in Bangladesh, their trends and associated large scale tropospheric conditions (Journal of Engineering Science, 2020)
Attempts have been made to study the heat waves along with the trends in Bangladesh and the large-scale tropospheric conditions over Bangladesh and neighbourhood responsible for generating heat waves in the country. Maximum temperature (Tmax) for the period 1981-2016 has been used in the study. Based on the definition of heat waves of Bangladesh Meteorological Department (BMD), the frequencies of days with Tmax≥360C and ≥ 380C have been computed and their trends are investigated to delineate the areas of heat waves in Bangladesh. During the period 1981-2016, Tmax≥360C is found to prevail annually for 79 days at Rajshahi, 51 days at Mongla, 50 days at Khulna in 2014 whereas it is found to prevail annually for 85 days at Chuadanga in 1992, 78 days at Jessore in 2010, 72 days at Satkhira in 1986 and 68 days at Ishurdi in 1995. In 2014, Tmax≥360C is found to exist annually for many days in western pat of Bangladesh in comparison to the eastern and costal region of the country. That is why year 2014 has been selected to study waves extensively. The study reveals that the monthly, seasonal and annual frequency of Tmax≥360C have increasing trends in Bangladesh except a very few places, having the highest increasing trends over southwestern part of the country with increasing rates of 0.816 day/year and 1.02 day/year, respectively at Mongla. The highest increasing trends over southwestern part may be due to the advection and penetration of higher Tmax due to northwesterly winds and less rainfall over the area. The seasonal and annual frequencies of Tmax≥380C have increasing trends at less than 50% stations in Bangladesh; some of the increasing trends of the seasonal and annual frequency of maximum temperature ≥380C are statistically significant up to 95-99% level of significance. The large-scale synoptic conditions show that heat waves are found to enter Bangladesh from the west/northwest due to the advection of higher Tmax from the west. Heat waves extend from west to east up to about central Bangladesh and a separate area of heat waves develop over the Chittagong Hill Tracts, the reason of which may be due to the diverging pattern of wind flows near the Chittagong Hill Tracts in the year of heat waves. Heat waves are absent along Sandwip-M.Court-Feni-Comilla region. In 2014, heat waves are found to be due to the influence of sub-tropical high over India and its extension over Bangladesh at the surface and at 850 hPa level with strong westerly/northwesterly winds at 850 hPa, influence of anticyclones persisting for many days over the Bay of Bengal at 300 hPa level, absence of upper level westerly troughs over India and BangladeshJournal of Engineering Science 11(1), 2020, 19-36